EFEKTIVITAS KERJA PEGAWAI PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT KOTA AMBON - Nurul Hazanah Rusli Husen; Wahab Tuanaya; Normawati Normawati; Hendry Selanno (Jurnal Ilmiah Global Education, 2023)
Employee work effectiveness is needed to produce good employee performance in the form of achievement and success in completing tasks. This research is a descriptive research type with a qualitative approach. The research method used by the author is to analyze data regarding the influence of regulations and human resources on employee effectiveness and to analyze the inhibiting factors of employee effectiveness from the two research focuses. The results of the study show that regulation and human resources have an effect on employee effectiveness, where based on these measurements it is known that the effectiveness of employee work in the Protocol and Leadership Communications Section is quite good, although there are several inhibiting factors that need to be addressed. Some of the factors that impede the effectiveness of the work of employees in the Protocol and Leadership Communications Section are the lack of consistency in implementing SOPs in one of the sub-sections, the lack of incentives given to employees, the lack of staff, the lack of operational vehicles, the leaders who are not assertive and some employees who are not disciplined.